2002
DOI: 10.1046/j.1442-2018.2002.00112.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of local application of cold or heat for relief of pricking pain

Abstract: The present study was designed to determine the effect of the application of cold or heat on the sensation of pricking pain based on autonomic responses. Electrical stimulation was applied to the antebrachium or brachium of subjects as an artificial pricking pain, and skin blood flow (BF) and skin conductance level (SCL) at the fingertip were measured. Pain sensation was evaluated using the visual analog scale. Pain stimulation produced a significant increase in SCL and a significant decrease in BF at both the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 37 publications
1
29
0
3
Order By: Relevance
“…Previous studies have documented an increase in both PTH and PTO with the use of cooling. 5 The fact that PTH and PTO were increased in a similar manner at both assessment site 1 (iced) and site 2 (non-iced) as well as the fact that PTH and PTO were significantly different between the EXP and CON ankles, may provide some mechanistic insight into the change in pain perception with ice application. Interestingly, some investigators have reported that with exposure to a cold environment (19˚C) for 30 min, plasma b-endorphin levels doubled.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Previous studies have documented an increase in both PTH and PTO with the use of cooling. 5 The fact that PTH and PTO were increased in a similar manner at both assessment site 1 (iced) and site 2 (non-iced) as well as the fact that PTH and PTO were significantly different between the EXP and CON ankles, may provide some mechanistic insight into the change in pain perception with ice application. Interestingly, some investigators have reported that with exposure to a cold environment (19˚C) for 30 min, plasma b-endorphin levels doubled.…”
Section: Discussionmentioning
confidence: 92%
“…For PTH1, significant ANOVA F ratios were reported for the main effects of ankle (F = 47. 5 Figure 1 The impact of ice application on nerve conduction velocity in experimental (EXP) and control (CON) ankles (data are mean (SD)). Timeline: pre, baseline; 15˚C, skin temperature cooling; 10˚C, skin temperature cooling; 15˚C, skin temperature with passive warming.…”
Section: Nerve Conduction Velocitymentioning
confidence: 99%
“…Results of the studies made in the area have shown that the cold treatment has increased the pain threshold (Koç et al 2006;Raynor et al 2005;Sarifakioğlu & Sarifakioğlu 2004). So, the cold treatments that are applied locally are used to reduce the edema and treat the pain by taking the inflammation process under control (Saeki 2002;Sarifakioğlu & Sarifakioğlu 2004;Van der Westhuijzen et al 2005). It has been stated that cold treatment over the area where surgical sutures are found after lumbar disc surgery reduces both the pain during first 24 hours and the need for morphine (Brandner et al 1996).…”
Section: Tens (Transcutaneous Electrical Nerve Stimulation)mentioning
confidence: 99%
“…[15] While medical drugs are being used for treating the somatic (physiological and emotional) dimension of the pain, non-pharmacological therapies aim to treat also the affective, cognitive, behavioral and socio-cultural dimensions of the pain. These non pharmacologic techniques, such as honey which decreases the need to analgesics via pain reduction after surgery [16] , cold diet which increased the pain threshold and reduce the edema and treat the pain by taking the inflammation process under control and at the same time allow the patient to get fluids in [17] , transcutaneous electrical nerve stimulation which help reducing the pain level and dosage of using analgesics by artificial stimulation of nerve fibers which try to stop or reduce the pain transmission [18] , relaxing therapy and distraction which increases the tolerance for pain and decrease the sensitivity for pain by getting the attention away from the pain [19] and also acupuncture can be used in an attempt to alleviate postoperative pain. [20] …”
Section: Discussionmentioning
confidence: 99%